Coastal Marine Heatwaves Detection in Java Using Satellite and In-situ - Willy Wulansari; Sugeng Widada; Lili Maslukah; Anindya Wirasatriya; Titi Sari (Universitas Diponegoro, 2026)
Global warming is driving an increase in the frequency and intensity of Marine Heatwaves (MHWs), which have a significant impact on coastal ecosystems. The detection of MHWs in Indonesia's coastal regions remains understudied due to limited long term in-situ data, while satellite products often have a coarse resolution that cannot capture local coastal dynamics. This study addresses this gap by detecting MHWs on the north coast of Java. It evaluates the performance of the Operational Sea Surface Temperature and Ice Analysis (OSTIA) product by comparing it against in-situ data from four Marine Automatic Weather Stations (Patimban, Karimunjawa, Rembang, and Paciran) from 2022–2024. To simulate an operational satellite based approach, MHWs were identified in the in-situ daily minimum temperature records using a climatology and 90th percentile threshold derived from the nearest satellite grid point. The statistical comparison reveals spatially variable differences in MHW frequency, duration, and total days between the two data sources. Event matching analysis indicates the best satellite performance at Paciran (Probability of Detection (POD)=0.74, False Alarm Ratio (FAR)=0.13), where most in-situ events were successfully captured. Conversely, the weakest performance was at Rembang (POD=0.43, FAR=0.59), where the satellite missed over half of the MHW days and exhibited a high false alarm rate. These findings demonstrate that significant MHWs occur in coastal regions, phenomena that may not be accurately captured by satellite data alone.